1995
DOI: 10.1111/j.1365-2958.1995.mmi_17030515.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of the pediocin operon of Pediococcus acidilactici PAC1.0: PedB is the immunity protein and PedD is the precursor processing enzyme

Abstract: The bacteriocin pediocin PA-1 operon of Pediococcus acidilactici PAC1.0 encompasses four genes: pedA, pedB, pedC and pedD. Transcription of the operon results in the formation of two overlapping transcripts, probably originating from a single promoter upstream of pedA. The major transcript comprises pedA, pedB, and pedC, while a minor transcript encompasses all of these genes and pedD. By deletion analysis and overexpression of pedB in Pediococcus pentosaceus we demonstrate that this gene encodes the pediocin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
119
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(126 citation statements)
references
References 38 publications
(37 reference statements)
6
119
0
1
Order By: Relevance
“…This result is in accord with the previous observation that the isolated immunity protein does not bind significantly to the parent bacteriocin CbnB2 in vitro (13). Genes for related immunity proteins have been found in other LAB bacteriocin-producing systems (17,(22)(23)(24)(25).…”
Section: Discussionsupporting
confidence: 82%
“…This result is in accord with the previous observation that the isolated immunity protein does not bind significantly to the parent bacteriocin CbnB2 in vitro (13). Genes for related immunity proteins have been found in other LAB bacteriocin-producing systems (17,(22)(23)(24)(25).…”
Section: Discussionsupporting
confidence: 82%
“…The ABC transporters involved in transportation of substrates containing double-glycinetype leader peptides are also responsible for proteolytic cleavage of the precursor. In vitro and in vivo experiments showed that the proteolytic domain was located near the N-terminus (Hivarstein et al, 1995;Venema et al, 1995). Analysis of the possible topology of these ABC transporters indicated that the proteolytic domain is probably located in the cytoplasm (H5varstein et a/., 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Genes encoding pediocin-like bacteriocins are cotranscribed with and/or in close vicinity to a gene encoding a cognate immunity protein which protects the bacteriocin producers from their own bacteriocin (2,10,19,27,28,37). Immunity genes that are not associated with bacteriocin genes have also been described (8).…”
mentioning
confidence: 99%